Kekerasan Cybersex Berbasis Gender Terhadap Perempuan Melalui Fitur Chatbot Anonymous Media Sosial Telegram - Nadhira Maulan Azizzah; Gialdah Tapiansari Batubara (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the legal regulations governing gender-based cybersex violence through the Anonymous Chatbot feature on Telegram social media within the framework of national law and legal protection for women as victims of gender-based cybersex committed through the Anonymous Chatbot feature on Telegram social media. The research method used is normative legal research with a descriptive-analytical approach through legislation. This study uses Feminist Legal Theory, Critical Legal Studies, and the theory of needs to explain power relations, legal constructs that impact the subordination of women, and the psychological factors behind cybersex behavior. This study uses a qualitative legal analysis method.The results of the study show that legal regulations on gender-based cybersex violence within the national legal framework are found in the Electronic Information and Transaction Law (ITE Law) and the Sexual Violence Criminal Law (TPKS Law). The ITE Law provides a basis for criminalizing immoral content in the digital space, but it is still limited and has the potential for multiple interpretations. The TPKS Law represents progress in the legal system with more comprehensive regulations because it not only focuses on criminal punishment but also on the victims. Legal protection for women as victims of gender-based cybersex committed through the Anonymous Chatbot feature on Telegram social media is currently still not optimal. This is because even though a national legal framework is in place, the existing legal framework still has weaknesses, one of which is that the regulatory text is still open to multiple interpretations. The multiple interpretations of the text have weakened legal protection for women who are victims of gender-based cybersex violence committed through the Anonymous Chatbot feature on Telegram social media.